Method-ological Mapping of Girlhood Studies: The Academic Landscapes of Girlhood. Issue 3 (1st December 2021) - Singh, Halle
Abstract: In this article, I report on a mapping project of the methods used in articles in Girlhood Studies: An Interdisciplinary Journal since its inception. By reviewing all articles published in this journal from June 2008 to December 2020, I investigate and visually map the methodological tools used in the production of knowledge with, for, and about girls and girlhood. Alongside visual representations of this data, I also seek to reinvigorate conversations about the importance of epistemological and methodological rigor in studies of girls and girlhood.